Peningkatan Kemampuan Mengelompokan Jenis Tumbuhan Berdasarkan Bentuk Daun Menggunakan Media flashcard Pada Siswa Tunarungu Kelas III SLBN Pembina Mamuju - Nurfitrah Ramadhani; St Kasmawati; Mustafa Mustafa (JURNAL ORTO DIDAKTIKA, 2023)
This research looks at class III deaf pupils at SLBN Pembina Mamuju's poor proficiency in classifying plant species based on the form of their leaves while studying science. The topic that needed to be solved in this research was how to improve categorizing plant species based on leaf shape in class III deaf students using flashcard media based on the outcomes of analysis between conditions. A test of action and documentation is the data gathering method. A class III deaf kid with the letters S served as the research subject. This study used an A-B-A research design using a single subject experiment (SSR). The study's findings suggest that classification of plant species will become easier. 1) In the baseline condition 1 (A1) is still low; 2) In the intervention condition (B) has increased; 3) In the baseline condition 2 (A2) has increased; 4) The analysis between conditions does not occur; however, the data show an overlap that significantly shifts the less capable category to the very capable category. According to the study's findings, class III deaf students' proficiency in classifying plant species based on the form of their leaves might be enhanced by using flashcard media.